A lysimetric study at Ludhiana for weather based irrigation Scheduling for kharif maize – Variety Vijay - VENKATARAMAN, S. (MAUSAM, 1981)
The seasonal march of evapotranspiration (ET) of kharif maize, in relation to pan evaporation (EP), rainfall and irrigation at Ludhiana in 1977 and 1978 are presented. The quantum of easily available field moisture for potential ET is seen to be 12 cm. The crop shows physiological senescence about 15 days from harvest. Peak consumption is from 5th to 12th week after sowing and the peak rate is 1.5 and 0.2 times that of EP. An irrigation schedule based on evaporimetry is indicated.